2004
DOI: 10.1096/fj.04-2621fje
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine receptor‐operated activation of TRP‐like channels can trigger critical Ca2+signaling events in pancreatic β‐cells

Abstract: There is little information available concerning the link between the ryanodine (RY) receptors and the downstream Ca(2+) signaling events in beta-cells. In fura-2 loaded INS-1E cells, activation of RY receptors by 9-methyl 5,7-dibromoeudistomin D (MBED) caused a rapid rise of [Ca(2+)]i followed by a plateau and repetitive [Ca(2+)]i spikes on the plateau. The [Ca(2+)]i plateau was abolished by omission of extracellular Ca(2+) and by SKF 96365. In the presence of SKF 96365, MBED produced a transient increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
(35 reference statements)
3
19
0
Order By: Relevance
“…We conclude that depletion of intracellular Ca 2ϩ stores fails to evoke significant SOCE in RINm5F cells. The lack of detectable SOCE is consistent with reports from insulinoma (44) and ␤-cells (20,27,(45)(46)(47) where SOCE was either very small or undetectable.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We conclude that depletion of intracellular Ca 2ϩ stores fails to evoke significant SOCE in RINm5F cells. The lack of detectable SOCE is consistent with reports from insulinoma (44) and ␤-cells (20,27,(45)(46)(47) where SOCE was either very small or undetectable.…”
Section: Resultssupporting
confidence: 90%
“…The results so far establish that agonists of RyR evoke Ca 2ϩ (or Mn 2ϩ ) entry that is independent of SOCE or voltage-gated Ca 2ϩ channels. Another study also showed that a RyR-selective agonist stimulates Ca 2ϩ entry via a SOCE-independent pathway in ␤-cells, although it speculated that it resulted from RyRmediated release of Ca 2ϩ from a non-ER store causing activation of Ca 2ϩ -permeable TRP (transient receptor potential) channels in the PM (20). Our subsequent experiments show that the Ca 2ϩ entry is mediated directly by RyR in the PM.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…These results suggest that the stimulation of TRPA1 eventually induces VDCC activation, and thereby increases in Ca 2+ influx. An association between TRP channels and VDCC has been reported in diverse systems, [38][39][40][41] including β-cells, 42) which showed that lowering the extracellular Na + concentration inhibited an islet amyloid polypeptide-stimulated TRPV4-mediated increase in [Ca 2+ ] i in cultured MIN6 β-cells. As TRPV4 is permeable to Ca 2+ and Na + to a similar extent, 43) the authors of that study concluded that islet amyloid polypeptide induces Na + entry via TRPV4, which thus stimulates membrane depolarization and Ca 2+ entry through VDCC.…”
Section: Fig 5 Gene Expression Of Trp Channels In Rinm5f Cells and mentioning
confidence: 95%